Three new species of Apiospora (Amphisphaeriales, Apiosporaceae) in China - Kunmin Yu; Hong Zhang; Kexin Cheng; Yulan Jiang (MycoKeys)
China is located in eastern Asia and has a large quantity and rich variety of bamboo resources. Bamboo resources also contain various fungal species such as Apiospora. The genus Apiospora is commonly used as plant pathogens, endophytes, and saprophytes, which are widely present in various host ranges around the world. The discovery of metabolites has been proven to play an important role in the pharmaceutical industry. Recently, 10 strains were isolated from bamboo in Guizhou Province, China, which were identified as five species of Apiospora based on multigene phylogenetic analysis of ITS, LSU, TEF1-α, and TUB2, and morphological observations, including two recognized species, Ap. arundinis and Ap. lophatheri, and three novel species, viz. Ap. bambusicaulis, Ap. bambusirimae, and Ap. bambusilentiginis. Illustrations and descriptions of these taxa are provided.